2018
DOI: 10.1080/20013078.2018.1541396
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale, cross‐flow based isolation of highly pure and endocytosis‐competent extracellular vesicles

Abstract: Isolation of extracellular vesicles (EVs) from cell culture supernatant or plasma can be accomplished in a variety of ways. Common measures to quantify relative success are: concentration of the EVs, purity from non-EVs associated protein, size homogeneity and functionality of the final product. Here, we present an industrial-scale workflow for isolating highly pure and functional EVs using cross-flow based filtration coupled with high-molecular weight Capto Core size exclusion. Through this combination, EVs l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 61 publications
(88 reference statements)
1
74
0
Order By: Relevance
“…Although TFF was introduced 10 years ago to isolate exosomes from large volumes of fluids, limited studies have been performed on the reproducibility of the method and functionality of the resulting exosomes [20,26,28,29,31]. We further analyzed multiple aspects of the reproducibility of the ExoSCRT™ technology.…”
Section: Reproducible Production Of Asc-exosomes By Tffmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TFF was introduced 10 years ago to isolate exosomes from large volumes of fluids, limited studies have been performed on the reproducibility of the method and functionality of the resulting exosomes [20,26,28,29,31]. We further analyzed multiple aspects of the reproducibility of the ExoSCRT™ technology.…”
Section: Reproducible Production Of Asc-exosomes By Tffmentioning
confidence: 99%
“…The TFF systems available for good manufacturing practice (GMP) are already in use and provide validated processes and GMP documents [15]. In fact, TFF was first introduced in 2010 for the isolation of exosomes according to size [16] and was gradually employed for exosome isolation or concentration in various experimental settings [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. More importantly, recent studies demonstrated the superior yield and activity of exosomes isolated by TFF compared with those isolated by ultracentrifugation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to ultracentrifugation, TFF achieves a greater EV yield, with a reduced amount of non-vesicular macromolecules contamination (Busatto et al, 2018). Other forms of flow-based purification such as Cross-flow isolation are also favorable over ultracentrifugation in terms of rate of production at large scale (McNamara et al, 2018). Ultimately, robust cost-effectiveness studies may be required to determine the optimal method of purification.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes contain the largest pool of extracellular RNA (exRNA) in biofluids, and are thus valued both for their diagnostic and therapeutic potential . The conventional method for exosome purification is ultracentrifugation, although many alternative strategies have been proposed, including TFF . Out of respect for the careful criterion used to define exosomes, we will refer to <100 nm EVs as small EVs (sEVs) rather than exosomes…”
Section: Introductionmentioning
confidence: 99%